2019
DOI: 10.1111/cdev.13233
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Discipline: Adolescents’ Institutional and Teacher Trust Predict Classroom Behavioral Engagement following Teacher Discipline

Abstract: This daily diary study examined how adolescents’ institutional and teacher‐specific trust predicted classroom behavioral engagement the day after being disciplined by that teacher. Within mathematics classrooms, adolescents (N = 190; Mage = 14 years) reported institutional and teacher‐specific trust and then completed a 15‐day diary assessing teacher discipline and behavioral engagement. The results indicated that, among adolescents with low teacher trust, discipline was unrelated to next‐day behavior. Contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 83 publications
0
34
1
Order By: Relevance
“…More recent research has yielded mixed results. Amemiya et al (2020) did not find gender differences in perceptions of trust in teachers or schools in a sample of middle school youth from the United States. Using data from Pathways to Desistance, McLean et al (2019) found that boys, relative to girls, had slower growth in perceptions of legitimacy from middle adolescence into early adulthood.…”
Section: Gender Differences In the Relationship Between Peer Antisocial Behavior And Perceptions Of School Authoritycontrasting
confidence: 55%
“…More recent research has yielded mixed results. Amemiya et al (2020) did not find gender differences in perceptions of trust in teachers or schools in a sample of middle school youth from the United States. Using data from Pathways to Desistance, McLean et al (2019) found that boys, relative to girls, had slower growth in perceptions of legitimacy from middle adolescence into early adulthood.…”
Section: Gender Differences In the Relationship Between Peer Antisocial Behavior And Perceptions Of School Authoritycontrasting
confidence: 55%
“…The trustor's role includes the propensity to trust which is established from past experiences and personal characteristics and is argued to be present at the beginning of a new relationship (Kikas et al, 2016;Amemiya et al, 2020). For example, teachers receiving new students in their school may have confidence that parents will work with them to the end, not because they know those parents are trustworthy, but because of the previous experiences with other parents.…”
Section: Propensity To Trustmentioning
confidence: 99%
“…For example, teachers receiving new students in their school may have confidence that parents will work with them to the end, not because they know those parents are trustworthy, but because of the previous experiences with other parents. The differences in the degrees of propensity to trust are directly related to differences in subsequent trust levels (Van Maele and Van Houtte, 2015;Amemiya et al, 2020).…”
Section: Propensity To Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…School resource officers are not the only aspects of schools that can affect adolescents' orientation to law. The trust that teachers build with students, taken together with students' trust in the broader school institution, can lead adolescents to become more positively engaged after receiving a disciplinary response (Amemiya, Fine, & Wang, ). Further, teacher fairness has been tied to adolescents' political understanding and community engagement (Claes, Hooghe, & Stolle, ).…”
Section: Policy and Research Implicationsmentioning
confidence: 99%